Comparative Safety Signal Assessment of Hospitalization Associated With the Use of Atypical Antipsychotics - Yunusa, Ismaeel; Teng, Chengwen; Karaye, Ibraheem M.; Crounse, Emily; Alsahali, Saud; Maleki, Nasim (Frontiers in Psychiatry, 2022)
Objective: To evaluate safety signals of hospitalizations associated with the use of atypical antipsychotics (AAPs). Method: We conducted a cross-sectional analysis to examine disproportionality in reporting hospitalizations suspected to be associated with 12 AAPs (aripiprazole, asenapine, brexpiprazole, clozapine, iloperidone, lurasidone, olanzapine, paliperidone, and pimavanserin, quetiapine, risperidone, and ziprasidone) using the FDA Adverse Event Reporting System (FAERS) database (from January 1, 2004, to December 31, 2021). We estimated reporting odds ratios (RORs) by comparing the odds of hospitalization occurring with a particular AAP to the odds of the same hospitalization occurring with all other drugs. In addition, we considered the presence of a significant safety signal when the lower limit of the 95% confidence interval (CI) of the ROR is greater than 1. Result: A total of 204,287 hospitalization cases were reported to the FDA for patients taking AAPs. There were significant safety signals of hospitalization associated with using clozapine (ROR, 2.88; 95% CI, 2.84-2.92), olanzapine (ROR, 2.61; 95% CI, 2.57-2.64), quetiapine (ROR, 1.87; 95% CI, 1.85-1.89), risperidone (ROR, 1.41; 95% CI, 1.39-1.43), aripiprazole (ROR, 1.34; 95% CI, 1.32-1.35), and ziprasidone (ROR, 1.14; 95% CI, 1.10-1.18). However, no safety signals were observed associated with using paliperidone, pimavanserin, iloperidone, asenapine, lurasidone, and brexpiprazole. Conclusions: This cross-sectional analysis of data from FAERs (2004-2021) suggested that users of clozapine, olanzapine, quetiapine, risperidone, aripiprazole, and ziprasidone were more likely to report being hospitalized than users of other AAPs .A cohort study comparing individual AAPs against each other is needed to delineate this safety signal further.